Integrating Cyber-Physical System toward Advanced Intelligent Industry: Features, Requirements and Challenges - Ferreira, Victoria de Los Angeles Reyes Cortés (2020)
Trabalho apresentado em International Conference on Industrial Engineering and Technology, 2020, Estocolmo, Suécia (digital)